Farm management - Hartley, John William A. (My University, 1892)
Introduction: The successful man in life is always the one who thinks before he acts; the one who uses intelligent forethought or speculative energy. Very few men gain wealth by chance, if they do it generally goes as easily as it came. To gain or retain wealth requires management. In no occupation of life do we find good management more necessary than on the farm; if any one must use speculative energy in order to be successful it is surely the farmers. But how few farmers, do we find scattered over our agricultural districts, who really manage a farm properly. To be sure they work and very hard too, but they do not do the right thing at the right time or in the right place; thus there is power wasted, energy lost, and no returns to bear expenses. The business of farming, rationally carried on, is one of the most complicated and difficult of all occupations; there are various things to be looked after. The farmer must not only know what his farm will produce best, but he must know whether or not there is a demand for the products he wishes to produce; he must watch the fluctuation in prices of farm products and sell the right thing at the right time.
Citation: Hartley, John William A. Farm management. Senior thesis, Kansas State Agricultural College, 1892.
Morse Department of Special Collections
Keywords: Farm management; Agriculture; Business; Theses; Manuscripts (documents)